IDENTIFICATION OF PLANT UTILIZATION IN THE LIFE CYCLE CEREMONY OF THE KAILI DA'A TRIBE IN UWEMANJE VILLAGE, KINOVARO DISTRICT, SIGI REGENCY - Syech Zainal Enal; Amirudin Kasim; Musdalifah Nurdin; Andi Tandra Tellu (Biology Department, Mathematics and natural science, Tadulako University, 2021)
The purpose of this study was to obtain information about the types of plants used by the Kaili Da’a tribe in life cycle ceremonies that are still preserved for generations in Uwemanje village, Kinovaro district, Sigi district. The research population is all people who live in Uwemanje Village, Kinivaro District, which are spread over 4 hamlets. The research method uses survey research with the help of interview questionnaires. Interviews were conducted on key respondents and general respondents. Key respondents were selected by purposive sampling as much as 10% of the population, namely the people who were considered to be the most knowledgeable about the ins and outs of this ceremony, such as Sando, traditional leaders, village heads and village priests. Meanwhile, general respondents are people who are recommended by key respondents with a record that they are at least 30 years old and are married or have a family. The data and information in this study were processed descriptively. Types of plants/plants used in life cycle ceremonies consist of 21 species, namely: rice (Oryza sativa L.), coconut (Cocos nucifera L.), banana (Musa paradisiaca L.), cocor duck (Kalanchoe pinata L.), areca nut (Areca catechu L.), turmeric (Curcuma domestica L.), nail paci (Lawsonia enermis L.), bogenvil (Boganvillea glabra L.), pandanus (Pandanus amarylifolius L.), jatropha (Jatropha curcas), forest basil ( Ocimum sanctum L.), moringa (Moringa oleifera L.), shallot (Allium cepa L.), Bengal grass (Eleusine indica L.), hibiscus (Hibiscus tiliaceus L.), peacock flower (Caesalpinia pulcherima L.), betel (Piper betle L.), keluwih (Artocarpus camansi L.), jasmine (Jasminum sambac L.), palm sugar (Arenga pinnata), and red sugar cane (Saccharum officinarum L.). The percentage of utilization of plant parts that are most directly utilized is the leaves which amount to 14 with a percentage of 65.66%, flowers amount to 4 to 16.67%, fruit to reach 3 to 12.5%. The least used parts are rhizomes, seeds, tubers, roots and stems with a percentage of 5.17%.